Applying service-dominant logic to recurrent release of software: an action research study. Issue 7 (1st August 2016) - Barqawi, Neda; Syed, Kamran; Mathiassen, Lars
Abstract : Purpose: Fierce competition drives software vendors to rely on Software-as-a-Service (SaaS) strategies and to continuously match new releases with customers' needs and competitors' moves. Such recurrent release practices pose specific challenges for software vendors which shape how they service customers. To address these challenges, this paper aims to apply service science to innovate strategies for SaaS release management. Design/methodology/approach: Based on action research methodology, the authors collaborated closely with Software Inc., an alias for a large multinational software provider, to apply service-dominant logic systematically, to analyze and improve its SaaS release management process and to support ongoing value co-creation with its customers. Findings: The authors provide a detailed account of how Software Inc. improved its SaaS release management practices; they extend current understanding of service innovation dynamics in SaaS environments and offer a model of value co-creation in SaaS release management grounded in the findings from Software Inc. Research limitations/implications: The research draws on a single case study with particular characteristics. Still, it allows for analytical generalizations with both theoretical and practical implications for how SaaS managers can improve recurrent release practices based on foundational service-dominant logic principles. Practical implications: The authors suggest that SaaS managers concentrate on knowledge-sharing with customers, ensure continuous communication among teams supporting the service, re-organize release management to enhance the value co-creation process, use technology to improve customer service experiences and use service mapping to improve release management and service quality. Originality/value: The authors bridge service-dominant logic principles and SaaS knowledge by demonstrating how service-dominant logic can be used to improve SaaS release practices and by offering conceptual and practical knowledge about value co-creation between customers and suppliers in SaaS contexts.